Alcohol abuse and stage of HIV disease in intravenous drug abusers. - Lake-Bakaar, G (1996)
Our objective was to identify factors that might correlate with human immunodeficiency virus (HIV) disease stage in intravenous drug abusers (IVDA). Particular attention was given to alcohol abuse. We accordingly explored in a cross-sectional study the relation between stage of HIV disease and age, sex, needle sharing, ethnicity, self-reported history of alcohol consumption and CAGE scores. IVDA from a single municipal hospital were subdivided into three groups according to HIV disease status. Group 1 comprised 42 individuals with AIDS; group 2 comprised 114 who were HIV positive but without AIDS; and group 3 comprised 52 who were HIV negative. Information on alcohol consumption and CAGE responses were obtained by questionnaire and interview. Discriminant analysis indicated that alcohol abuse, assessed either by self-reported consumption or by CAGE scores, was significantly more common in the AIDS group than in either the HIV positive or the HIV negative groups, when controlled for age, sex, and needle sharing status. The relative risk of AIDS was 3.8 times higher in the heavy drinkers than in moderate drinkers. Needle sharing was also more common in the AIDS group than in the HIV positive or HIV negative groups when the other factors were controlled for. AIDS was more common in black than white IVDA, and this increased frequency did not appear related to alcohol consumption since the distribution of heavy drinkers within each category of HIV disease did not differ within the ethnic groups. These data indicate that a history of heavy alcohol consumption is more common in IVDA with AIDS than in IVDA at earlier stages of HIV disease.